Penerapan Sistem Akuntansi pada Perusahaan “Mie Baso Akung” - Aiva Tyanka Farahdiva; Fahmi Ilham; Fiqri Cahya Maulana; Neng Anisa Nurul Fadilah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the implementation of the accounting system at Mie Baso Akung, which is part of the Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The main focus of this report is to explain the accounting system in the cash sales, purchasing, inventory, and payroll and wages sections. In its work, the author uses qualitative methods through interview techniques and also observation. Based on the results of the study, it was found that most of the processes are still carried out manually by the owner who does not comply with the proper procedures. This indicates the need for the implementation of a more structured system to improve operational efficiency. In addition, this study also identified obstacles in inventory management, which is very important to maintain the availability of raw materials and production efficiency. Therefore, Mie Baso Akung needs to implement a more detailed accounting information system and better internal control in order to improve operational efficiency that can help Mie Baso Akung in managing its finances and operations more effectively.